UJI VALIDITAS MEDIA ANIMAL LIFE CYCLE (ALC) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS III - Siti Zulaikah; Wendri Wiratsiwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to test the validity of the Animal Life Cycle (ALC) learning media developed to improve critical thinking skills of grade III students. Animal Life Cycle (ALC) media is a 3-dimensional miniature learning media adopted from Diorama media which was created with the aim of depicting real scenery, so that learning materials are clearer and easier for students to understand so that they can encourage students' critical thinking skills. Validation was carried out by two experts, namely material experts and media experts using a Likert scale-based assessment instrument. This type of research is development research with a quantitative descriptive approach. Data collection techniques used observation sheets, interviews, questionnaires, test sheets, and validation sheets. The validation results by material experts obtained a score of 95% (very valid category) and media experts obtained a score of 85% (very valid category). The overall average validation score of the Animal Life Cycle (ALC) media was 90%, which indicates that this media is in the "very valid" category and is suitable for use in the learning process. Thus, the Animal Life Cycle (ALC) media is proven to meet the aspects of content, presentation, and technical feasibility, and has great potential to support the achievement of students' critical thinking skills. These findings are expected to be the basis for further development and implementation of interactive and innovative media in elementary school learning.